HARDINESS AS AN IMPORTANT CRITERION FOR ENSURING THE PERSONALITY PSYCHOLOGICAL SECURITY - Karapetyan, L. M. (Modern Psychology, 2020)
Theoretical aspects of personality hardiness are analyzed in this article as an important criterion for ensuring psychological security. The article touches upon issues of hardiness, psychological security and stability. The concepts of hardiness are analyzed in the context of various psychological approaches, where its fundamental and particular definitions are singled out. The hardiness is an essential condition for ensuring psychological security and stability, thus the need for studying this phenomenon in modern conditions gets more actualized. On the basis of the theoretical-methodological analysis, it is proposed to include the component of the stability in the context of studying the issue of hardiness.
Keywords: hardiness; hardy attitudes; stability; aspects of personality stability; psychological security